Pelatihan Bisnis Online Bagi Pelajar Pondok Pasantren Modern Saifullah an nahdiyah - Putri wahyuni; Dedy Lazuardi; Muammar Rinaldi; Bambang Sutejo; Ihdina Gustina (Jurnal Pengabdian Masyarakat Eka Prasetya, 2023)
During this pandemic, there have been many significant changes, including business. Business during the Covid-19 pandemic has become more or less a challenge and opportunity for business people, including the younger generation (millennial generation). This training provides insight and knowledge about the importance of learning entrepreneurship or business like what many business people do, such as creating new products or adding product variations. During the Covid-19 pandemic, millennials are also required to be digitally literate and creative in business, and not only compete but collaborate